SISTEM PENUNJANG KEPUTUSAN LOKASI TERBAIK JUAL BAKSO DI KOTA MALANG DENGAN METODE BASIS DATA FUZZY - Fahri, Agis Arizal; Widarti, Dinny Wahyu (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2015)
The meatballs are very popular and can be found throughout Indonesia from the cart street vendor to big restaurant. Emerging entrepreneurs meatballs good food at a roadside Malang and building a medium-sized or large like kiosks, shops and malls most locations are not chosen properly and appropriately.The purpose of this research is a decision support system by determining the best location in town selling meatballs poor with fuzzy database method. The method applied in this study is developing a system (SDLC) Software Development Life Cycle.Based on test results concluded that the Decision Support System Application provides information determining the best location to display the options that facilitate decisions on employers in determining the best location and the right to run a business Keywords: Decision Support Systems, Location, Database Fuzzy